2005
DOI: 10.1104/pp.105.064386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calreticulin on Viral Cell-to-Cell Movement

Abstract: Cell-to-cell tobacco mosaic virus movement protein (TMV MP) mediates viral spread between the host cells through plasmodesmata. Although several host factors have been shown to interact with TMV MP, none of them coresides with TMV MP within plasmodesmata. We used affinity purification to isolate a tobacco protein that binds TMV MP and identified it as calreticulin. The interaction between TMV MP and calreticulin was confirmed in vivo and in vitro, and both proteins were shown to share a similar pattern of subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 73 publications
3
114
0
2
Order By: Relevance
“…In addition, several calreticulins were found to play important roles in plant resistance to virus. For examples, papaya (Carica Papaya) CpCRT gene increased plant resistance to papaya ringspot virus (Shen et al, 2010), and the intra-cellular transportation of tobacco mosaic virus was suppressed in tobacco plants overexpressing a corn gene ZmCRT1 (Chen et al, 2005). These results indicated that calreticulins played key roles in plant defense responses and resistance to environmental stresses (Jia et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, several calreticulins were found to play important roles in plant resistance to virus. For examples, papaya (Carica Papaya) CpCRT gene increased plant resistance to papaya ringspot virus (Shen et al, 2010), and the intra-cellular transportation of tobacco mosaic virus was suppressed in tobacco plants overexpressing a corn gene ZmCRT1 (Chen et al, 2005). These results indicated that calreticulins played key roles in plant defense responses and resistance to environmental stresses (Jia et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…and corn ZmCRT1 in defense responses (Chen et al, 2005), but rice Q9SP22, OsCRO1 and BAG89479 are associated with cold stress resistance (Arun et al, 2004;Komastu et al, 2009). In Group II, tobacco ACH72686 and papaya CpCRT participate in plant defense responses (Lu et al, 2010;Shen et al, 2010), while tobacco NtRPL60 and caster bean AAB71420 play roles in plant growth and development (Denecke et al, 1995;Coughlan et al, 1997).…”
Section: Cluster Analysis Of Crt Proteinsmentioning
confidence: 99%
“…Chen et al (2005) suggested calreticulin engagement in TMV translocation between ER and PD. Calreticulin is a protein, which was localized in PD due to N-terminal signal peptide (Baluska et al 1999;Michalak et al 1999).…”
Section: Mp Tmv and Its Partners In Movementmentioning
confidence: 99%
“…Calreticulin is a protein, which was localized in PD due to N-terminal signal peptide (Baluska et al 1999;Michalak et al 1999). Chen et al (2005) showed that calreticulin interacts with TMV MP and over-expression of this protein in transgenic plants determines TMV relocation from PD to microtubules and thus cell-to-cell transport of the virus. Potential role of calreticulin in PD capacity was discussed also by Boevink and Oparka (2005), who underlined the ability of PD to modify thanks to MP TMV-CRT cooperation by changes in cell wall structure.…”
Section: Mp Tmv and Its Partners In Movementmentioning
confidence: 99%
“…Plasmodesmata-associated kinase (PAPK) specifically phosphorylates TMV MP at its C-terminus in vitro (Lee et al, 2005). Calreticulin, a calcium-sequestering ER-resident protein, binds MP in vitro and interferes with TMV movement in overexpressing transgenic plants (Chen et al, 2005). Actin elements (Hofmann et al, 2007) and myosins (Amari et al, 2014) are required for MP-plasmodesmata interaction.…”
Section: Effects Of Tmv Movement Proteinmentioning
confidence: 99%